Pengaruh Sanksi Pajak, Tax Amnesty, dan Pengetahuan Pajak terhadap Kepatuhan Pajak - Rizal Nasrullah Al Abbas; Tumirin Tumirin (JIATAX (Journal of Islamic Accounting and Tax), 2019)
This study aims to determine the effect of tax sanctions, tax amnesty, tax knowledge on the level of personal taxpayer compliance. This study uses a quantitative approach. The sample in this study was 80 WPOP registered in North Gresik Small Taxpayer Office using a purposive sampling technique. The data analysis technique uses multiple linear regression. The results of this study indicate that there is a significant effect of tax sanctions on WPOP taxpayer compliance which is registered at North Gresik KPP. There is no effect of tax amnesty on WPOP taxpayer compliance registered at North Gresik Small Tax Office. Tax knowledge has a significant effect on WPOP taxpayer compliance that is registered at North Gresik KPP.